STRATEGIES TO INCREASE PASSENGER SATISFACTION DURING THE PANDEMIC AT ADI SOEMARMO AIRPORT - Astri Desiana; Ardhianiswari Diah Ekawati (Jurnal Scientia, 2023)
Since the establishment of COVID-19 as a pandemic, there have been various changes that must be felt by airport service users related to the implementation of health protocols and the adaptation of new habits. This causes changes that must be felt by airport service users, especially passengers related to their experience while at the airport which can affect passenger satisfaction with the quality of service provided by the airport. This study aims to determine the key drivers of passenger satisfaction during the COVID-19 pandemic. The study was conducted on passengers who made domestic departures through Adi Soemarmo Airport during the period March 2020 – December 2021 using the Airport Service Quality (ASQ) questionnaire based on the Airport Council International (ACI) framework. The data was then analyzed using the PLS-SEM method. Environmental variables, airport facilities, and security are variables that become key drivers, so that the management of Adi Soemarmo Airport can focus on these dimensions to be able to increase passenger satisfaction through efforts to improve the indicators that describe these dimensions.